Manju The Composition of the Empire and the cultural anthropological nature of the Ch’ing’s ruling class: A case study of the Manju women - Kai He, A. (Journal of Oriental Studies, 2021)
For more than a century, the trends in the study of Ch’ing history have been relatively uniform throughout the world. In particular, the anthropological characteristics of the ruling class of the Ch’ing Empire are defined as equivalent to the cultural characteristics of the social group of the ruled class. Through this article, the author hopes to show readers a brand-new concept of country and culture. That is, through the analysis of women, the uniqueness of the Manju Group and its national nature are discussed. From the linguistics point of view, the Manju circle speaks the Manchurian language. In terms of cultural attributes, JianZhou Jurchen belongs to the cultural category of Tunguska. Social life characteristics are completely different from Han Chinese, Mongol, Chinese Muslim, Tibetan and other cultural groups in the Empire. From the perspective of religious cultural anthropology, JianZhou Jurchen Group is a Shamanism believer. Furthermore, Eight Banner, a military organization that absorbed military-civilians of different races and cultural backgrounds through surrender and capture, was completely redefined as a JianZhou Jurchen-style civiliazation with a unified ideology during the imperial rule for more than two hundred years. Therefore, the author advocate that Manju people and their culture should not be confused with the cultural characteristics of other groups in the Ch’ing Empire, and should be clearly separated and studied. Key words: Manju (Manchu), Ch’ing (Qing), Jurchen, Tungus, JianZhou, women, Matrilineal Clan Society.